Perempuan, Tradisi, dan Ketahanan Budaya: Praktik Pelestarian Kain Tenun Bira di Tengah Arus Modernisasi - Ramadhani, Annisa; Wahyuni, Ekawati Sri; Sjaf, Sofyan (CV. Social Politic Genius (SIGn), 2025)
Bira Woven Fabric, a maritime cultural heritage in South Sulawesi, faces a serious threat of extinction due to the pressures of modernization. This study aims to deconstruct the social mechanisms underlying this preservation crisis, moving beyond purely economic or technical analyses. Employing a qualitative approach and Pierre Bourdieu’s practice theory framework, this study analyzes how the dialectical interaction among habitus, capital, and field shapes the practices of women weavers. Key findings indicate that this crisis is rooted at three levels. First, the formation of a cleft habitus (habitus clivé) within the weavers, who are caught between loyalty to tradition and economic rationality. Second, the systematic devaluation of their cultural and symbolic capital in the contestation against the dominance of economic capital within the social field. Third, their subordinate position within a field governed by the logic of tourism and patriarchal structures. This study concludes that weaving preservation is not merely a technical issue but a political struggle to change the “rules of the game” within the field. The research suggests that successful interventions require a holistic approach that extends beyond economic strengthening, focusing on the revitalisation of habitus, the revaluation of cultural capital, and, most importantly, the structural reform of the field itself.